Construction of Ta'lim Muta'allim Counseling Based on the Book of Imam Al-Zarnuji: A Hermeneutical Study - Habsy, Bakhrudin All; Rizal, Agus; Madoni, Ely Roy; Rachmania, Nita; Kadri, Nursyuhaidah Mohd (Letiges, 2024)
The book Ta'lim Muta'allim by Sheikh Imam Al-Zarnuji contains life guidelines for seeking practical knowledge and mardhatillah. This research aims to develop the discipline of counselling based on Islamic values ??and describe and analyze the construction of counselling in the book Ta'lim Muta'allim. This research uses a qualitative approach with an eclectic type of hermeneutics to understand the text in depth and make correct articulations to capture and interpret the meaning of the book Ta'lim Muta'allim. Primary data includes an analysis of the book Ta'lim Muta'allim by Sheikh Imam Al-Zarnuji. In contrast, additional data was obtained through interviews and observations at Islamic boarding schools that use and teach the book Ta'lim Muta'allim. The validity used includes triangulation, intersubjective validation, and peer review. Eclectic hermeneutic analysis is carried out in several stages, namely the verstehen (understanding) stage, grammatical interpretation and psychological interpretation stage, integration of text and context stage, truth relativism stage, wirkungsgeschichte (awareness) stage, bildung stage and critical reflection stage. Ta'lim Muta'allim's counselling construction presents a form of counselling based on Islamic values ??that meets the postulates of scientific discipline rules, namely internal coherence, conformity with reality and functionality when applied theoretically and practically. This research has realized counselling constructions such as the basic philosophy of counselling, main concepts of counselling, goals of counselling, counselling relationships and mechanisms for change in Ta'lim Muta'allim counselling.